Permohonan Hak Asuh Anak Bagi WNA yang Berdomisili di Luar Negeri - Suaib Lubis; Puput Chairani (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
The research was conducted at the Stabat State Religious Court. This research was conducted qualitatively by carrying out several stages. Data collection techniques by observing and interviewing directly in the Stabat Religious Court. Based on the results of the study it can be concluded in determining the custody of minors that in this case the best interest of the child at this time is to live with the mother because in reality the children have begun to adjust to the environment they are in now and get care, care, and get education well. The Panel of Judges determined custody of minors in this case fell to the mother with no intention of alienating the child from the father. As a review of Islamic law in terms of determining the custody of minors to the mother in its legal considerations the Panel of Judges considers the benefit of the child. The Assembly in interpreting its legal considerations in establishing child custody is oriented to maintaining the five main points in Islamic law and by seeing who is better able to guarantee the realization of the child's best interests and to realize the objectives of syara 'law (maqashid asy-syari'ah) in maintaining the child's religion , take care of the soul of the child, preserve the child's mind, nurture offspring, and preserve the child's property. Keywords: Application for child custody, Foreign Citizens